Glucose-6-Phosphate Dehydrogenase (G6PD) Status in Neonatal Jaundice and its Relationship with Severity of Hyperbilirubinemia - Akhter, Nilufa; Begum, Noorzahan; Khan, Waqar Ahmed (Journal of Bangladesh Society of Physiologist, 2010)
Background: G6PD deficiency is one of the common inherited enzymatic disorder associated with high incidence of severe neonatal hyperbilirubinemia. Objectives: To observe G6PD status in male, term neonates with jaundice and its correlation with serum level of bilirubin. Methods: This cross sectional study was conducted on 90 male, term neonates with jaundice, age ranged from 3 to 12 days (Group B) in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) between July 2007 to June 2008. On the basis of total serum bilirubin (TSB) level, study group was further divided into B1(TSB <15mg/dl), B2(TSB 15-20mg/dl) and B3 (TSB>20mg/dl). For comparison age and sex matched 30 apparently healthy neonates (Group A) were also included in the study. Erythrocyte G6PD level was measured by Spectrophotometric method by using kit of Randox. Serum bilirubin level was measured by standard laboratory technique. For statistical analysis ANOVA, independent sample "t" test and Pearson's correlation coefficient test were performed as applicable by using SPSS windows version-12. Results: In this study, erythrocyte G6PD levels were significantly lower in moderate (p<0.01) and severe (p<0.001) hyperbilirubinemic group in comparison to that of control group . However, this enzyme level was lower in mild group compared to that of control but the difference was statistically non significant. Again, this enzyme levels were significantly lower in moderate (p<0.05) and severe (p<0.01) group than that of mild group and also between severe and moderate hyperbilirubinemic group (p<0.05). In this study, G6PD enzyme deficient were found in 1(3.33%) and 6(20%) subjects of group B2 and B3 respectively. Though, percentage of the subjects with enzyme deficiency were higher in severe group ( B3 ) compared to that of moderate group( B2 ) but the difference was statistically not significant. However, no enzyme deficient patient were found in control group (A) and mild hyperbilirubinemic group (B1). Serum bilirubin level showed significant (p<0.05) positive (r=+.429) correlation with erythrocyte G6PD level in control group (A). On the other hand, this level was negatively correlated with G6PD enzyme in groups B1 (r= -.127), B2 (r=-.120) and B3 ( r= -.671) but significant negative correlation in group B3 (p<0.01). Conclusion: The results of the study revealed that severity of hyperbilirubinemia depends on degree of G6PD deficiency. Therefore, early detection of this enzymopathy and close surveillance of the affected neonates may be important in reducing the complications of severe hyperbilirubinemia. Key words: Glucose-6-PD, Hyperbilirubinemia, Neonates DOI: 10.3329/jbsp.v4i2.4176 J Bangladesh Soc Physiol. 2009 Dec;4(2): 71-76